The islamic credit card based on ujrah concept: conceptual review - Md Faruk, Abdullah; Abubakar, Balarabe (2020)
Islam is a way of life that seeks to protect the human being from financial harm through prohibiting riba, maysir, and gharar. Islamic credit card is one of the alternative banking products offered by Islamic financial institutions to replace the conventional credit card. The Islamic credit card was initially based on the Inah concept. However, this concept was criticized by both contemporary and classical Islamic jurists, especially in the Hambali, Maliki, and Hanafi school of thought. Therefore, some Islamic banks of Malaysia offer a better alternative, developing the credit card on the concept of Ujrah, which is less ambiguous among Islamic scholars. This study will explore the background of Islamic credit card base on the concept of Ujrah. It will then further discuss the justification for the permissibility of the concept. Finally, this paper will highlight the issues related to the practice of Ujrah in Islamic credit card operations. The findings indicate that the credit cards based on Ujrah (fee) are permitted from the Sharia perspective as long as they do not involve any element of riba (interest). However, it involves Shariah issues on its practice of ibra (rebate) and penalty charge. To fulfil the objectives of the study, it will refer to the Quran, Hadith, classical Islamic jurisprudence, juristic opinion of Islamic scholars, Shariah standards of international Islamic standard-setting bodies, and other policy documents of the Islamic banks.